Auxins Upregulate Expression of the Indole-3-Pyruvate Decarboxylase Gene in Azospirillum brasilense - Vande Broek, Ann (American Society for Microbiology, 1999)
Transcription of the Azospirillum brasilense ipdC gene, encoding an indole-3-pyruvate decarboxylase involved in the biosynthesis of indole-3-acetic acid (IAA), is induced by IAA as determined by ipdC-gusA expression studies and Northern analysis. Besides IAA, exogenously added synthetic auxins such as 1-naphthaleneacetic acid, 2,4-dichlorophenoxypropionic acid, and p-chlorophenoxyacetic acid were also found to upregulate ipdC expression. No upregulation was observed with tryptophan, acetic acid, or propionic acid or with the IAA conjugates IAA ethyl ester and IAA-l-phenylalanine, indicating structural specificity is required for ipdC induction. This is the first report describing the induction of a bacterial gene by auxin.